Proposed Maintenance Planning for Screw Press Machines Using the Reliability Centered Maintenance (RCM) Method at PT. SIR - Yudistia, Fiki; Suherman, Suherman; Hamdy, Muhammad Ihsan; Harpito, Harpito; Devani, Vera (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2026)
PT. SIR is one of the manufacturing companies engaged in processing oil palm fruit into crude palm oil (CPO) and Palm Kernel (PK) with a processing capacity of 45 tons/ hour. From the results of interviews and observations, it was found that the problem that occurred in the company was frequent sudden damage to the srew press machine which resulted in the machine and the production process stopping. The method used in this research is Reliability Centered Maintenance (RCM). The purpose of this research is to identify critical components on the srew press machine, develop a proposed maintenance schedule for each critical component at the Screw Press station, and provide recommendations on the type of periodic maintenance activities for critical components at the Screw Press station. From the results of the research obtained 5 critical components of the srew press machine which are recommended improvements from namely, bearings, shaft press, worm srew, press cage, and spur gear obtained Proposed maintenance schedule for each critical component, namely, on the bearing component the average damage time is 403 hours and the proposed maintenance schedule is 320 hours. Shaft press components average damage time 649.29 and proposed maintenance schedule 470 hours. Worm Srew components average damage 365.58 hours and proposed maintenance schedule 285 hours. Press Cage components average damage 737.5 hours and proposed maintenance schedule 570 hours. Spur Gear components average damage time 671.2 hours and proposed maintenance schedule 520 hours.